Identification of Soil-Transmitted Helminth Eggs on the Fingernails of Roof Tile Craftsmen in Urek-Urek Village, Gondanglegi District - Yuniarreza Satriani; Erni Yohani Mahtuti; Previta Zeizar Rahmawati (poltekkes kemenkes pontianak, 2026)
Soil-transmitted helminths (STHs) are intestinal parasites transmitted through contaminated soil and remain a significant public health concern, particularly among workers who frequently come into direct contact with soil, such as roof tile craftsmen. This study aimed to identify the presence of soil-transmitted helminth eggs on the fingernails of roof tile craftsmen in Urek-Urek Village, Gondanglegi District. A qualitative descriptive study design was employed using a purposive sampling technique. The study population consisted of 35 roof tile craftsmen, of whom 29 respondents met the inclusion criteria. Fingernail samples were examined using the 10% potassium hydroxide (KOH) sedimentation method. The results showed that 2 out of 29 respondents (6.9%) tested positive for Soil-Transmitted Helminth eggs, specifically Ascaris lumbricoides. One respondent (R16) was found to have fertile Ascaris lumbricoides eggs, while another respondent (R17) had infertile Ascaris lumbricoides eggs. Cross-tabulation analysis between personal hygiene practices and examination results demonstrated that respondents with moderately adequate personal hygiene accounted for both positive findings (9.5%). Most respondents with inadequate hygiene practices did not use footwear while working and washed their hands and feet only with water without soap. These findings indicate that poor personal hygiene and inadequate use of personal protective equipment may increase the risk of STH contamination among roof tile craftsmen. Therefore, health education regarding proper handwashing practices and the use of personal protective equipment, such as footwear and gloves during work activities, is strongly recommended to reduce the risk of STH infection.